Candida rugosa lipase immobilization on modified mesoporous kit-6 from rice husk as biocatalyst in esterification for butyl butyrate - Noorulsyahidaini Golbaha, 1988- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Kimia)) - Universiti Teknologi Malaysia, 2017